Elemental Fusion : Unlocking the Science Lab (A Game-Based Mobile Learning Application about Chemistry Subject for Form 4 and Form 5 Students) - Abu Bakar, Nurul Syahirah; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2026)
Chemistry is one of the subjects that can be taken in Malaysia Certificate of education (SPM). There are several topics that are causing difficulty to remember and feel more challenging to learn Chemistry. Therefore, an educational mobile game learning application named Elemental Fusion: Unlocking The Science Lab with gamification approach is developed to help Form 4 and Form 5 students improve their chemistry skills that combines the immersive experience of an escape room with interactive chemistry quizzes. Elemental Fusion application has three modules including Recap module, Game module, and Quiz module. Besides, Multimedia Mobile Content Development (MMCD) methodology is used to develop the Elemental Fusion: Unlocking The Science Lab application. System Usability Scale (SUS) method is used to obtain the results of a user acceptance test. It gets 78.08% positive feedback through this testing. In conclusion, Elemental Fusion is an application that is suitable for learning Chemistry.